Conditions and Results of Innovative Development in Latin America and Russia: a Comparative Analysis - S. M. Vasin (Мир новой экономики)
Relevance. The problems of innovative development and effective innovation management have long been a priority in the world economy and, most likely, their relevance will be in the mainstream for many years to come. The paper analyses the provision and performance of innovation processes in nine countries of Latin America and Russia in order to identify the most successful economies in terms of approaches and effects of innovation activity in different evaluation planes. The specifics of structural efficiency of innovation activity components in crisis and post-crisis periods have been studied.Research methods — comparative analysis of the structure of the global innovation index (GII) in the target countries in 2020 and 2023, multiple regression analysis of the impact of resources and innovation results on the level of the global innovation index, t-statistics to compare the innovation dynamics of the target countries in the period from 2020 to 2023.Scientific novelty — on the basis of statistical approach the specifics of innovative development of Latin American countries and Russia and regularities of achieving different levels of the global innovation index in the crisis and postcrisis periods are revealed.The results of the study show that the leaders in terms of GII level among Latin American countries are Brazil, Chile, Uruguay, Colombia and Argentina, and the most important for the formation of GII are the components of innovation results — the development of technology and knowledge economy, as well as the results of creative activity. Ecuador and Peru are the countries with the most detached innovation development trajectory. In the year of the covid crisis the components of institutions and market development were particularly developed, in the post-covid year — the level of business development, as well as human capital and research. Finally, the dynamics of GII in Russia is closest to Brazil in most components. The results obtained are of practical value as a reference point in the development and adoption of economic and political decisions on the reallocation and concentration of resources for the development of the most effective components of GII.